Karakteristik Whey Limbah Dangke dan Potensinya Sebagai Produk Minuman dengan Menggunakan Lactobacillus acidophilus FNCC 0051 - Fatma Fatma; Soeparno Soeparno; Nurliyani Nurliyani; Chusnul Hidayat; Muhammad Taufik (agriTECH, 2012)
Dangke whey has not been widely utilized.  Dangke  whey handling is required  for the prevention of environmental pollution, especially  in Enrekang. Evaluating the characteristics of dangke whey is the initial step of dangke  whey handling. Complete data about the dangke whey would be  scientific information for researchers or the public to further the utilization. Nutritional value of dangke whey allows the use of  Lactobacillus acidophilus FNCC 0051 to be processed into  beverage  products. This research objectives were to investigate the characteristics of whey from dangke waste, which were obtained from milk protein separation by using lyophilization of papaya latex, and it also to evaluate the potential of dangke whey as beverage product by using Lactobacillus acidophilus FNCC 0051. A commercial fermented beverages product is used as a comparison, based on the activity  of growth/bacteria numbers, lactic acid and pH. Milk was added with enzyme solution (lyophilized latex) on the level of 0.4 to 1% (v/v). The best level was used for the production of the fermented whey beverage products. Whey was mixed with tapioca level of 0, 0.35, 0.7, 1.05, and 1.4%, and was heated by stirring for 5 minutes at temperature of 70oC. The whey was pasteurized at the temperature of 80oC for 30 minutes. The whey was cooled, and inoculated with L.acidophilus at the level of 1, 3, 5, and 7%, and incubated at 37°C for 8, 12, 16, 18, and 24 hours, respectively. The characteristics of whey dangke were as follows: the solid total was 6.95 ± 0.23%, lactic acid was 0.1 ± 0.003%, fat was 0.2 ± 0.05%, protein was  0.63 ± 0.009%, lactose was 5.08 ± 0.009%, pH was 6.31 ± 0.01, and viscocity was 0.19 ± 0.004 poise. Dangke whey is potential as a beverage products with the addition of  Lactobacillus acidophilus with quality similar to the commercial fermented beverage after incubated for 16 hours, with the addition of inoculum level of 5% and tapioca level of 0.35% based on the activity of growth, lactic acid and pH. ABSTRAKWhey dangke belum banyak dimanfaatkan. Penanganan whey dangke sangat diperlukan untuk pencegahan pencemaran lingkungan khususnya di Kabupaten Enrekang. Evaluasi karakteristik whey dangke merupakan langkah awal penanganan whey dangke. Data yang lengkap tentang karakteristik whey dangke akan menjadi informasi ilmiah bagi para peneliti ataupun masyarakat untuk pemanfaatan whey dangke lebih lanjut. Nutrisi whey memungkinkan penggunaaan Lactobacillus acidophilus FNCC 0051 untuk diolah menjadi produk minuman. Penelitian ini  bertujuan mengetahui karakteristik whey limbah dangke, diperoleh dari pemisahan protein susu dengan menggunakan getah pepaya liofilisasi serta mengetahui potensi whey dangke sebagai produk minuman menggunakan Lactobacillus acidophilus FNCC 0051 dengan menggunakan produk minuman fermentasi komersial sebagai pembanding, berdasarkan aktivitas pertumbuhan/jumlah bakteri, kandungan asam laktat dan pH. Susu ditambahkan larutan enzim (getah liofilisasi) level 0,4 - 1% (v/v), dan level terbaik digunakan untuk  pembuatan produk minuman whey fermentasi. Whey dicampur tepung tapioka  level 0, 0,35., 0,7., 1,05 dan 1,4% dan dipanaskan sambil diaduk selama 5 menit suhu 70oC. Whey selanjutnya di pasteurisasi suhu 80oC selama 30 menit. Setelah dingin diinokulasi L.acidophilus level 1, 3, 5, dan 7% serta diinkubasi  suhu  37oC selama 8, 12, 16, 18 dan 24 jam. Karakteristik whey dangke adalah; total padatan 6,95±0,23%, asam laktat 0,1±0,003%, lemak 0,2±0,05%, protein 0,63± 0,009%, laktosa 5,08 ±0,009%, pH 6,31±0,01 dan viskositas 0,19±0,004 poise. Whey dangke berpotensi sebagai produk minuman dengan penambahan Lactobacillus acidophilus dengan kualitas yang hampir sama dengan produk minuman fermentasi komersial setelah diinkubasi selama 16 jam, penambahan level inokulum 5%  dan penambahan level tapioka 0,35% berdasarkan aktivitas pertumbuhan, asam laktat dan pH.